"Because There's Just Something About That Menthol": Exploring African American Smokers' Perspectives on Menthol Smoking and Local Menthol Sales Restrictions. Issue 2 (22nd August 2020) - D'Silva, Joanne; O'Gara, Erin; Fryer, Craig S; Boyle, Raymond G
Abstract: Introduction: Local governments are pursuing policies to limit the availability of menthol cigarettes at the point-of-sale. Although African Americans are disproportionately impacted by menthol cigarettes, little is known about African American smokers' perspectives on emerging menthol policy. The purpose of this study was to fill a gap in the literature by exploring African American adult (25+) smoker perspectives on menthol and a local menthol sales restriction. Methods: In-depth semi-structured interviews were conducted with African American smokers ( n = 27) in the Minneapolis–St. Paul area June–September 2017. Interviews explored smoking behaviors, harm perceptions, perspectives of menthol in the community and reactions to local menthol sales restrictions. The framework method guided identification of key themes and synthesis of findings. Results: Almost all (96%) participants smoked Newport cigarettes. The majority of participants indicated that menthol cigarettes were more harmful than non-menthol cigarettes, citing strength and additives and because they were targeted to African Americans. Some participants were receptive to policy change while others viewed the policy as inconvenient and unfair. Overall, there was a lack of understanding of the policy's intended public health impact. Some participants indicated that the policy would have no impact on their purchasing or smoking behaviors while others who were contemplating quitting noted that a menthol restriction was encouragement to prompt a quit attempt. Conclusions: Sales restrictions can provide a unique opportunity to persuade menthol smokers to quit. Efforts are needed to increase awareness and support of these policies as well as to support African American menthol smokers achieve cessation. Implications: There is growing momentum to restrict local menthol tobacco sales; however, little is known about perceptions among populations most impacted. In Minneapolis–St. Paul, where menthol restrictions were passed in 2017, African American smokers expressed limited awareness and uneven policy support. While some participants were unconvinced the restriction would impact smoking, others indicated it would encourage decreased consumption and prompt quit attempts. There is a need for public education to increase awareness of menthol's harms, to help menthol smokers quit, and to increase support for menthol policies.